Landscape diversity of tourist routes in Skole Beskids = Ландшафтна різноманітність туристичних маршрутів Сколівських Бескид - Burianyk, O.; Melnyk, A. (Journal of Education, Health and Sport, 2016)
Burianyk O., Melnyk A. Landscape diversity of tourist routes in Skole Beskids = Ландшафтна різноманітність туристичних маршрутів Сколівських Бескид. Journal of Education, Health and Sport. 2016;6(6):337-350. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55696 http://ojs.ukw.edu.pl/index.php/johs/article/view/3583 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 10.06.2016. УДК 627 (234.421.1) LANDSCAPE DIVERSITY OF TOURIST ROUTES IN SKOLE BESKIDS O. Burianyk Ivan Franko National University of Lviv A. Melnyk Uniwersytet Kazimierza Wielkiego w Bydgoszczy ЛАНДШАФТНА РІЗНОМАНІТНІСТЬ ТУРИСТИЧНИХ МАРШРУТІВ СКОЛІВСЬКИХ БЕСКИД О. Буряник Львівський національний університет імені Івана Франка А. Мельник Університет Казимира Великого в Бидгощи Abstract There was done the overview of tourist and recreational researches in physico-geographical area of Skole Beskids. Based on the field researches and the use of GIS technologeis, there was constructed the landscape map of the researched area and indicated the existing marked and equipped tourist routes nowadays.There was described the landscape diversity on the level of landscape areas and array of two ecological and cognitive routes, seven ecological and cognitive trails, two road routes, one bike- and equestrian trails. Additionaly there was suggested the map of routes and described two new ecological and cognitive routes and two new road routes. Keywords: Skole Beskids, hiking trails, landscape complexes, landscape diversity. Анотація Здійснено огляд туристичних і рекреаційних досліджень у фізико- географічному районі Сколівські Бескиди. На основі польових досліджень і використання ГІС-технологій укладено ландшафтну карту на досліджувану територію і прив’язано до неї існуючі на сьогодні промарковані і облаштовані туристичні маршрути. Описано ландшафтну різноманітність на рівні ландшафтних місцевостей і стрій двох еколого-пізнавальних маршрутів, семи еколого-пізнавальних стежок, двох автомаршрутів, одного вело- і одного кінного маршрутів. Запропоновано перебіг шляхів і описано два нових еколого-пізнавальних маршрути та один новий автомобільний маршрут. Ключові слова: Сколівські Бескиди, туристичні маршрути, ландшафтні комплекси, ландшафтне різноманіття.